2003
DOI: 10.1002/jbt.10094
|View full text |Cite
|
Sign up to set email alerts
|

Goitrogenic activity of p‐coumaric acid in rats

Abstract: The effects of three natural phenolic acids (caffeic, ferulic, and p-coumaric) on the rat thyroid gland were examined in a 3-week oral-treatment study. Forty male Wistar albino rats, divided into groups of 10 rats each and fed iodine-rich diet, were administered by gastrointestinal tube saline (control), caffeic acid, ferulic acid, or p-coumaric acid at a dose level of 0.25 micromol/kg/day for 3 weeks. The mean absolute and relative thyroid weights in caffeic, ferulic, or p-coumaric acid groups were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Despite its enormous usefulness and potential health benefits, flavonoids emerge as phytochemicals of great concern due to their antithyroidal and goitrogenic effect. It has previously been reported that the consumption of flavonoids and some phenolic acids by experimental animals induced enlargement and histological changes in the thyroid gland [5][6][7][8][9] . Studies on effects of tea extracts on thyroid physiology are not available though it is used as whole beverage rather taking any single component of it, so this is very plausible to investigate the effect of total green tea extract on rats.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its enormous usefulness and potential health benefits, flavonoids emerge as phytochemicals of great concern due to their antithyroidal and goitrogenic effect. It has previously been reported that the consumption of flavonoids and some phenolic acids by experimental animals induced enlargement and histological changes in the thyroid gland [5][6][7][8][9] . Studies on effects of tea extracts on thyroid physiology are not available though it is used as whole beverage rather taking any single component of it, so this is very plausible to investigate the effect of total green tea extract on rats.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that the consumption of flavonoids and some phenolic acids by experimental animals induced enlargement and histological changes in the thyroid gland. [8][9][10][11][12] Previous study reported that after a 13-weeks oral administration of polyphenone-60 (P-60), which is green tea extract (GTE) catechins, it was found that this treatment at high dose induced goiters in rats. 13,14 However, studies on the un-fractionated tea extracts on thyroid physiology are not available though tea is used as whole beverage rather than taking any single component of it, so it is very essential to study the effect of un-fractionated green and black tea extracts on rats.…”
Section: Introductionmentioning
confidence: 99%
“…However, m-coumaric acid has been suggested as the weakest antioxidant among hydroxycinnamic acids ( 22 , 23 ). Although oral supplementation of p-coumaric acid had significant goitrogenic effect in rat models ( 24 ), the impact of m-coumaric acid on thyroid has not been studied. In the present study, we found that p-coumaric acid levels were not different between the two groups, while m-coumaric acid levels were significantly higher in GD groups, compared to those in controls.…”
Section: Discussionmentioning
confidence: 99%